Geotechnical Challenges in Slope Stability: Experimental Investigation of Coconut Fiber Reinforcement Under Seismic Loading - Doddamani V.C.; Rakaraddi P.; Ray A.; Rai R.; Khandelwal M. (My University, 2025)
Geotechnical challenges in contemporary engineering necessitate the construction of structures on poor soils and vulnerable slopes due to limited land availability. The stability of soil slopes under seismic conditions is crucial for designing safe infrastructures. Conventional slope reinforcement techniques, such as geosynthetics, are effective but costly. This study explores the use of coconut fibers as a cost-effective, temporary reinforcement for improving slope stability under seismic loading. The research involved horizontal and vertical shake table tests on slopes of varying heights and angles, both with and without surcharge loads. Coconut fibers were mixed into the soil at different percentages to assess their effectiveness in reducing displacements and settlements during seismic events. Linear Variable Differential Transformers (LVDTs) measured displacements at various heights on the slopes. Results indicate that slopes reinforced with coconut fibers exhibit significantly reduced vertical and horizontal displacements compared to unreinforced slopes under both vertical and horizontal seismic loading. The reinforced slopes showed improved stability, particularly under higher surcharge loads and increased shaking frequencies. This study demonstrates that coconut fibers can serve as an effective, eco-friendly reinforcement method for temporary slope stabilization, offering a sustainable alternative to synthetic materials. The findings contribute to the broader understanding of natural fiber applications in geotechnical engineering, especially for regions prone to seismic activities. © The Author(s) 2025.